2021
DOI: 10.1007/s10826-021-02125-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Parental Variables and Youth’s Career Decision-Making Self-Efficacy: A Meta-Analysis

Abstract: Despite extensive research on career decision-making self-efficacy (CDMSE) in relation to youth's career development and outcomes, the relative influence of different parental variables on youth's CDMSE remains relatively unclear. Thus, this meta-analysis sought to compare correlational findings concerning the influence of three types of parental variables-parental cognitions, parenting behaviors, and parentchild relationships-on youth's CDMSE. This meta-analysis also aimed to examine differences in how matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…This finding is essential for learners at a young age in making an informed decision that might have a fundamental impact on their employability. The finding supports previous researchers (To et al, 2022;Parola & Marcionetti, 2022) who also established the role of parents in their children's career paths. Consequently, the research supports Epstein's theory in terms of stakeholders that must form part of the decisions made to improve children's academic achievement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is essential for learners at a young age in making an informed decision that might have a fundamental impact on their employability. The finding supports previous researchers (To et al, 2022;Parola & Marcionetti, 2022) who also established the role of parents in their children's career paths. Consequently, the research supports Epstein's theory in terms of stakeholders that must form part of the decisions made to improve children's academic achievement.…”
Section: Discussionsupporting
confidence: 91%
“…They can then get the opportunity to observe how their children relate to each other and with their educators, which is important for a child's educational development (Bromley & Yazdanpanah, 2021). Likewise, parental support influences children's decisions in career choices (Parola &Marcionetti, 2022;To et al, 2022). Indeed, children who receive parental support at home are more likely to make a good career choice compared to children who do not receive support.…”
Section: Western Perspectivesmentioning
confidence: 99%
“…Along with the constant and fast-paced changes in contemporary career environments, researchers have paid significant attention to career development and the psychological factors associated with its development, particularly with regard to an individual's career decision-making self-efficacy (Taylor & Betz, 1983;To et al, 2021). According to self-efficacy theory proposed by Bandura (1977Bandura ( , 1986, self-efficacy can refer to an individual's belief in his or her ability to enact the behaviors necessary for making performance attainments.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…In regards to how attachment security impacts career development, Wright and colleagues (e.g., Wright & Perrone, 2008; Wright & Perrone, 2010; Wright et al, 2014; Wright, 2017) have argued for the inclusion of attachment as a relational variable that should be considered within the SCCT framework, and have demonstrated direct empirical support for this notion. For example, there is evidence that secure attachment to parents relates to aspects of students’ career development, such as career exploration and planning (Boerchi et al, 2019; Vignoli et al, 2005) and self-efficacy pertaining to career decisions and tasks (O’Brien et al, 2000; To et al, 2021; Wolfe & Betz, 2004). In particular, Wright and Perrone (2008) suggest that attachment security would reflect in individuals’ ability to be more willing to approach and participate in learning experiences to progress career development, rather than experiencing distress or avoiding such experiences.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Wright and Perrone (2008) suggest that attachment security would reflect in individuals’ ability to be more willing to approach and participate in learning experiences to progress career development, rather than experiencing distress or avoiding such experiences. Moreover, To et al (2021) found in a recent meta-analysis that parental cognitions, parenting behaviors, and parent-child relationship quality were associated with the career development of their children. These authors reason that secure relationships with parents might allow students to experience emotional support, which in turn would contribute to greater confidence in and commitment towards career decision making.…”
Section: Introductionmentioning
confidence: 99%